New topology of shunt hybrid power filter for harmonic mitigation and re-utilization of harmonic filter current as useful power - Mohamad Asghaiyer, Mohamed Omran (2023)
Power electronic appliances are recently used widely in industrial, commercial, and home sectors; these appliances include diode and thyristor rectifiers, and variable speed drive systems. When these appliances are connected to the grid, they generate harmonics in the current and voltage waveform which contributes to the degradation of the system efficiency and deterioration of the overall system performance due to an increase of effective peak value and also the rms current in some devices. Conventional passive power filters (PPF) for harmonic mitigation have inherent problems, while purely active power filters (APF) have the disadvantages of higher costs and ratings. Hybrid active filters (HPF) inherit the efficiency of PPFs and the improved performance of APFs, and thus, constitute a viable improved approach for harmonic compensation. An eight different HPF topology is composed of one APF and PPF in series or shunt or combination. Nevertheless, among the existing mitigation HPFs, the shunt LC HPF is the most effective against current harmonics problems due to its feasibility for harmonic current compensation. However, it cannot perform satisfactory dynamic reactive power compensation because reactive power varies from time to time. Furthermore, to have low impedances at high frequencies, the capacitor of this filter needs to be large which will be influenced seriously by the source inductor. In this study, a new topology of shunt RLC-HPF is introduced to improve the efficiency of current harmonic reduction and perform power factor (PF) correction through reactive power compensation via the provision of a low impedance path through the inductor (for low frequencies) and low impedance through the capacitor (for high frequencies).. The effectiveness of HPF is strictly dependent on how quickly and accurately the detection of reference harmonic current, DC-link capacitor voltage regulation, and current control is achieved. The shunt HPF was designed based on synchronous reference frame strategy (SRF) and self-tuning filter (STF) to develop the operation of the filter under non-ideal (unbalanced and/or distorted) source voltage conditions. As for its controller, switching signals to drive the voltage source inverter (VSI) of the shunt APF adaptive hysteresis current controller (AHCC) are used. Also, proportional-integral (PI) and back propagation neural network (BPNN) controllers are developed to maintain a constant voltage across the DC-link capacitor so that the shunt APF can precisely inject the desired referred currents back into the harmonic power system. The shunt HPF performance is validated for all possible conditions of source and load by simulation using MATLAB/ Simulink environment. The simulation results obtained by the STF -SRF strategy with BPNN controller showed excellent achievement when compared to SRF with PI controller in the mitigation of current harmonics, PF enhancement, and DC voltage regulation. As a result, the minimum total harmonic distortion (THD) values of the source current recorded clear advantages of the STF-SRF strategy (1.8 %) over the existing SRF strategy (10 %), especially in dealing with non-ideal source voltage conditions. Furthermore, the encouraging findings have led to the correction of the PF to 0.999 using STF-SRF in contrast to 0.842 with the SRF strategy. Moreover, the DC-link capacitor voltage was properly regulated and maintained at the respective desired values under all cases with the BPNN controller, while the PI controller failed to be regulated. Ultimately, the main aim of the new HPF topology is the improvement of PF and reducing harmonic current, as well as re-utilization of the extracted harmonic filter current via conversion to useful power to feed the RL load within the limitation of the IEEE-519-2014 standards.